2020
DOI: 10.3389/fonc.2020.01645
|View full text |Cite
|
Sign up to set email alerts
|

Standardizing Health Outcomes for Lung Cancer. Adaptation of the International Consortium for Health Outcomes Measurement Set to the Spanish Setting

Abstract: Purpose: Lung cancer (LC) and its treatment impose a significant burden on patients' life. However, patient-centered outcomes are rarely collected during patient follow-up. Filling this gap, the International Consortium for Health Outcomes Measurement (ICHOM) developed a standard set of variables for newly diagnosed LC patients. In order to facilitate the use of this standard set, the project aims to adapt it to the Spanish setting. Methods: The variables (instrument and peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 32 publications
(41 reference statements)
0
20
0
Order By: Relevance
“…Survival measures (e.g., overall and disease-free survival) were commonly reported as measures of value by patients, clinicians, and other stakeholders involved in the development of the outcome sets in the included studies ( n = 21) [ 39 , 40 , 42 , 44 , 49 , 51 , 55 60 , 63 65 , 68 71 , 74 , 75 ]. In addition, some studies reported that measuring all-cause mortality is superior to disease or cause-specific mortality, which is less meaningful to patients and harder to capture due to the non-availability or limited reliability of data related to the cause of death [ 42 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Survival measures (e.g., overall and disease-free survival) were commonly reported as measures of value by patients, clinicians, and other stakeholders involved in the development of the outcome sets in the included studies ( n = 21) [ 39 , 40 , 42 , 44 , 49 , 51 , 55 60 , 63 65 , 68 71 , 74 , 75 ]. In addition, some studies reported that measuring all-cause mortality is superior to disease or cause-specific mortality, which is less meaningful to patients and harder to capture due to the non-availability or limited reliability of data related to the cause of death [ 42 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…In some studies ( n = 3), the Patient Health Questionnaire was used as a complementary tool for the generic tools to measure anxiety and depression aspects [ 43 , 56 , 57 ]. The European Quality of Life (EuroQoL) tool was mainly used in studies of cancer [ 39 , 60 , 65 , 72 , 74 , 75 ]. Longitudinal data and measurements of PROMs were used in almost all studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The value of pharmacist-led team care in pharmacotherapies has been demonstrated in numerous studies ( Yamamoto et al, 2018 ; Escudero-Vilaplana et al, 2020 ; Satsuma et al, 2020 ; Ji et al, 2021 ; Jia et al, 2021 ; Marzal-Alfaro et al, 2021 ; Miura et al, 2021 ; Xu et al, 2021 ). The results of this study revealed that pharmacist-urologist collaborative management can also improve care for patients with CRPC receiving enzalutamide in an ambulatory care setting.…”
Section: Discussionmentioning
confidence: 99%